Suboptimal use of hormonal therapy among German men with localized high-risk prostate Cancer during 2005 to 2015: analysis of registry data - Abera, Semaw Ferede; Bedir, Ahmed; Glowka, André; Vordermark, Dirk; Medenwald, Daniel (BMC cancer, 2022)
Background This study assesses the use of hormonal therapy to treat high-risk localized prostate cancer (HRLPCa) cases diagnosed between 2005 and 2015. Methods All N 0-X M 0 with ≥T 3a, or PCa cases with poorly differentiated feature (equivalent to Gleason score ≥ 8), diagnosed between 2005 and 2015 were extracted from German population-based cancer registries. Cases treated by surgery or chemotherapy were excluded. Description of hormonal therapy use by HRLPCa cases’ profile was presented. Relative risk (RR) was computed with a log-link function to identify factors associated with hormonal therapy use among radiotherapy-treated HRLPCa cases. Results A total of 5361 HRLPCa cases were analyzed. Only 27.6% (95% confidence interval [CI]: 26.4–28.8%) of the HRLPCa cases received hormonal therapy in combination with radiotherapy. The use of combined hormonal therapy and radiotherapy varied from 19.8% in Saxony to 47.8% in Schleswig-Holstein. Application of hormonal therapy was higher for the locally advanced cases compared to the poorly differentiated cases (relative risk [RR] = 1.28; 95%CI: 1.19, 1.37). Older patients showed a slightly increased use of hormonal therapy (RR for a 10-year age increase = 1.09; 95%CI: 1.02, 1.16). Compared to PCa cases from the most affluent residential areas, cases from the least affluent (RR = 0.71; 95%CI: 0.55, 0.92) and medium (RR = 0.75; 95%CI: 0.58, 0.96) areas had decreased use of hormonal therapy. The introduction of the German S3-guideline did not make a marked difference in the uptake of both hormonal therapy and radiotherapy (RR = 1.02; 95%CI: 0.95, 1.09). Conclusion This study found a low use of hormonal therapy among HRLPCa patients treated without surgery. The introduction of the German S3-guideline for prostate cancer treatment does not seem to have impacted hormonal therapy use.